The Diabetes Care Cascade in Sri Lanka: An Analysis of Losses, Disparities, and Opportunities for Improved Health System Outcomes - Ravindra P. Rannan-Eliya; Nilmini Wijemunige; H. M. M. Herath; Prasadini Perera; Vajira H.W. Dissanayake; Bilesha Perera; Shanti Dalpatadu; Sarath Samarage; Anuji Gamage (Health Systems & Reform)
Sri Lanka has one of the highest prevalence rates of diabetes, and improving diabetes control is a national priority. The care cascade framework, a tool for evaluating diabetes control and identifying system gaps, has not been assessed nationally in Sri Lanka. This study addresses this gap using data from a nationally representative longitudinal cohort. Using 2018–2019 data from the Sri Lanka Health and Ageing Study (SLHAS), we evaluated the diabetes care cascade, estimating levels of (i) prevalence, (ii) testing, (iii) diagnosis, (iv) awareness, (v) treatment, (vi) medication adherence, and (vii) control. Logistic regression assessed factors associated with step performance, and concentration indices quantified socioeconomic inequalities. Performance was benchmarked against other countries. In 4,827 participants the weighted diabetes prevalence was 23.2%. Of those with diabetes, 86.0% had been tested, 62.3% diagnosed, 58.6% aware, 44.7% treated, and 20.6% (hemoglobin A1c, HbA1c < 8.0%) and 12.4% (HbA1c < 7.0%) controlled. Older adults and those with hypertension achieved higher rates at all steps, while disparities by gender, education, location, and body mass index were minimal. Concentration indices confirmed pro-rich inequity from testing to treatment but revealed no significant inequity in control. Sri Lanka outperforms most low- and middle-income countries (LMICs) in testing, diagnosis, treatment, and disparities in coverage, reflecting underlying system strengths. But only one in five Sri Lankans with diabetes achieve control, with significant losses post-treatment. High diagnosis and treatment rates alone are insufficient; strategy must shift toward understanding the reasons for poor control. and improving treatment outcomes, a lesson with wider relevance.